Customer Experience Evaluation on Implementation Kredit Pasti Mudah (KPM) Application AT PT. Bank XYZ - Christian Vieri Sasmita; Wahyu Sardjono (Journal of Economics and Business UBS, 2023)
Customer Experience is a perception that is felt by customers where they interact with applications, products, services from the brand of a product. Applications used by customers such as smartphones, websites, computer software, and so on. Currently application KPM that implemented CRM system at PT. BANK XYZ use has not been maximized. There is an obstacle that happening on Customer Experience in the use of KPM application and it’s affecting the Customer Satisfaction. The purpose of this study is to find out what variables contribute in the practices that the company have an obstacle between Customer Experience and Application in CRM system at PT. BANK XYZ with Factors Analysis and building a model for using CRM implementation process in current KPM application and determine the CRM Strategy at PT. BANK XYZ in the future using Regression Analysis. This research shows that in this study there are new 7 factors that has been founded using Factor Analysis in the Customer Experience sides namely Sales Utilization, Customer Regain, Customer Rewards, Technical Contribution, Customer Segmentation, Customer Personalization, Customer Retention. The result from seeing a Regression Analysis result we could apply in practice as we could make a strategy to reinforces the strength and decreasing its weakness of the application at PT. BANK XYZ.